The SWOT Analysis of Policy Implementation on Competence Development at Bandung Regency - Nasyika Fitriarifahrul Sholiha; Ratna Meisa Dai; Deasy Silvya Sari (Universitas Padjadjaran, 2021)
Bandung Regency is a Regional Government that has the most State Civil Apparatus (ASN) in West Java Province which has a very low ASN Professionality Index (IP) is 27.85. In order to improve the competence of ASN, Bandung Regency implements a competency development policy based on Regent Regulation Number 63 of 2017. This article aims to analyze the policy implementation strategy by the Personnel Agency and Human Resources development (BKPSDM) in competency development in the Bandung Regency Environment. The research method uses descriptive qualitative. The data collected was obtained through interviews and observations. The author found that BKPSDM has implemented competency development policies with SWOT analysis with the results that BKPSDM Bandung Regency is in quadrant II, which is in a position between opportunities and weaknesses, so it is necessary to take a diversification strategy in implementing competency development policies.